2020
DOI: 10.1155/2020/2914579
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology‐Based Approach to Revealing Biological Mechanisms of Qingkailing Injection against IschemicStroke: Focusing on Blood‐Brain Barrier

Abstract: Ischemic stroke is the most common type of cerebrovascular accident worldwide. It causes long-term disability and death. Qingkailing (QKL) injection is a traditional Chinese patent medicine which has been clinically applied in the treatment of ischemic stroke for nearly thirty years. In the present study, network pharmacology combined with experimentation was used to elucidate the mechanisms of QKL. ADME screening and target prediction identified 62 active compounds and 275 targets for QKL. Topological screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…The BBB is a highly specific vascular interface that maintains brain homeostasis by separating the blood chamber from the central nervous system. The value of BBB ≥ −0.3 was considered to have a moderate-to-strong degree of central penetration [ 34 ]. As stated by the recommended conventional ADME parameter (absorption, distribution, metabolism, and excretion), oral bioavailability (OB) is used as a significant pointer to identify the characteristics of bioactive molecules for oral administration, and the screening critical condition was set to OB ≥ 30% [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…The BBB is a highly specific vascular interface that maintains brain homeostasis by separating the blood chamber from the central nervous system. The value of BBB ≥ −0.3 was considered to have a moderate-to-strong degree of central penetration [ 34 ]. As stated by the recommended conventional ADME parameter (absorption, distribution, metabolism, and excretion), oral bioavailability (OB) is used as a significant pointer to identify the characteristics of bioactive molecules for oral administration, and the screening critical condition was set to OB ≥ 30% [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…In general, one compound is considered permeable across the BBB when its BBB permeability is larger than −0.30. Active flavonoids were acquired by the following criteria: OB ≥ 30%, DL ≥ 0.18, and BBB ≥ −0.3 [ 9 , 10 ]. Active compounds of flavonoids reported publicly in recent five years were also taken into analyses from 1 st January 2016 to 30 th May 2021.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the authors inspected the neuroprotective effect of refined QLI (made up of baicalin, geniposide, cholic acid, and hyodeoxycholic acid) against CI/RI and detected that the effect was related to its attenuation of brain damage and cell apoptosis and activation of glial cells by modulation of the PI3K/Akt, TNF, NOD-like receptor, NF-κB, and TLR signaling pathways ( Ma C. et al, 2020 ). Zhang et al combined a network pharmacology–based approach with the experiment to probe the biological mechanisms of QLI against CI on the BBB and found that QLI alleviated BBB dysfunction, regulated expression of TJ, and modulated HIF-1α/MMP-9 activation ( Zhang S. et al, 2020 ). With good efficacy and pharmacological effect, QLI is considered the first choice for the clinical treatment of CI/RI.…”
Section: Chm Preparations For Ci/rimentioning
confidence: 99%